A multidisciplinary approach for the management of temporomandibular joint disc displacement without reduction - Rashmi Kishor Jaggad; Ina Bhupesh Patel; Ronak Hemant Choksi; Khyati Bhavik Gosai (Wolters Kluwer Medknow Publications, 2019)
The temporomandibular joint (TMJ) is one of the primary components of the complex masticatory system. Any disturbance in the joint due to congenital or acquired causes such as trauma, pathology, or functional disturbance affects the masticatory system. This case report highlights the management of condylar hypoplasia due to trauma by forceps delivery which led to TMJ dysfunction and chronic disc displacement without reduction. A combination of stabilization appliance and arthrocentesis using platelet-rich plasma along with patient education has been proved effective for the conservative management of patients with chronic disc displacement and TMJ dysfunction.